2013
DOI: 10.1080/00207594.2013.793800
|View full text |Cite
|
Sign up to set email alerts
|

The emotional Stroop task and emotionality rating of negative and neutral words in late Thai–English bilinguals

Abstract: The current study investigated how emotions are represented in the lexicon of late Thai-English bilinguals and a comparison group of native English speakers. Two tasks were used. In the emotional Stroop task, which taps into an automatic early lexical level of processing, the bilingual participants did not display the same automatic level of activation in their second language (L2) as in their first language (L1). In the emotionality-rating task, which involves a later, more in-depth conscious level of process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 23 publications
5
67
3
1
Order By: Relevance
“…The other three studies that measured the emotional effects worked with late bilinguals, who started to learn the second language at the age of 6-7 or later (Eilola et al 2007;Eilola & Havelka 2010b) and in formal, educational settings (Winskel 2013). Eilola et al (2007) and Eilola and Havelka (2010b) have found mutually concurring results: a significant effect of word type, and non-significant effects of language and interaction.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The other three studies that measured the emotional effects worked with late bilinguals, who started to learn the second language at the age of 6-7 or later (Eilola et al 2007;Eilola & Havelka 2010b) and in formal, educational settings (Winskel 2013). Eilola et al (2007) and Eilola and Havelka (2010b) have found mutually concurring results: a significant effect of word type, and non-significant effects of language and interaction.…”
Section: Discussionmentioning
confidence: 88%
“…In conclusion, it seems that the changes in physiological (re)activity are not always mirrored in subjective experience. Winskel (2013) investigated the effects of language proficiency on emotional interference. Twenty negative and twenty neutral emotion and emotional words were used to compare a native English group from Australia with Thai-English bilinguals from Thailand.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contradictory research findings have also been reported in the emotional Stroop task in bilinguals. For instance, studies with late Thai-English bilinguals revealed identifiable differences between the automatic activation of emotional content in L1 and L2 emotion words (Winskel, 2013). Furthermore, mixed results were observed within one single study with empirical evidence from different tasks.…”
Section: Introductionmentioning
confidence: 99%